2023
DOI: 10.1097/lvt.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Costs of pediatric liver transplantation among commercially insured and Medicaid-insured patients with cholestasis in the US

Abstract: Children with rare cholestatic liver diseases, such as Alagille syndrome, progressive familial intrahepatic cholestasis, and biliary atresia typically require liver transplantation (LT). The objective of this analysis was to assess the economic burden of LT on these patients. Health care resource utilization and costs associated with pediatric LT were retrospectively assessed using insurance claims data from the US IBM MarketScan Commercial and Medicaid databases collected between October 2015 and December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…In post-LT period, the total direct medical cost was peak during the first year after surgery and gradually decreased, similar to previous studies in the US [24] and Canada [25]. Drug cost was the highest among all categories in this study which were mostly contributed by immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In post-LT period, the total direct medical cost was peak during the first year after surgery and gradually decreased, similar to previous studies in the US [24] and Canada [25]. Drug cost was the highest among all categories in this study which were mostly contributed by immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, the reference price is approximately 470,000-625,000 THB during this period, consisting of 410,000-565,000 THB for the admission during the transplant operation and 60,000 THB for the outpatient care within 3 months after LT. Nevertheless, the cost of LT in this study was lower than the reported cost in North America [24,25].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Our study is thus foundational in the realm of cost analyses in pediatric LT, and emphasizes the pertinence of valuebased health care to this population. [27,28] In addition to total cost, an understanding of cost distribution is central to resource stewardship and high-value care efforts. Our study demonstrated that LT was dominated by "other" costs-a composite of room cost, operating room time, and various fees not related to ancillary patient care services.…”
Section: Discussionmentioning
confidence: 99%